2020
DOI: 10.1155/2020/9817095
|View full text |Cite
|
Sign up to set email alerts
|

Resistin Is Increased in Periodontal Cells and Tissues: In Vitro and In Vivo Studies

Abstract: Resistin, a proinflammatory adipokine, is elevated in many inflammatory diseases. However, little is known about its performance in periodontitis. The present study is aimed at evaluating resistin expression and synthesis in periodontal cells and tissues under inflammatory/microbial stress in addition to its effects on the periodontium. In vivo, 24 male rats were randomly divided into two groups: control and ligature-induced periodontal disease. After 6 and 12 days, animals were sacrificed to analyze gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Bacterial infection can stimulate to secretion of inflammatory mediators and proteases, and gingival epithelial cells can remove them by innate and acquired immune responses [ 38 ]. In addition, some scholars have also found that leptin and resistin have a certain impact on the pathogenesis of periodontitis [ 39 , 40 ]. What’s more, one of the biological explanations for obesity negatively affects the progression of periodontitis and the response to periodontal therapy may be also due to the unaffected leptin, resistin and adiponectin levels after the periodontal non-surgical treatment [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial infection can stimulate to secretion of inflammatory mediators and proteases, and gingival epithelial cells can remove them by innate and acquired immune responses [ 38 ]. In addition, some scholars have also found that leptin and resistin have a certain impact on the pathogenesis of periodontitis [ 39 , 40 ]. What’s more, one of the biological explanations for obesity negatively affects the progression of periodontitis and the response to periodontal therapy may be also due to the unaffected leptin, resistin and adiponectin levels after the periodontal non-surgical treatment [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, many adipokines are produced not only in the adipose tissue by adipocytes but also by other cells and tissues during obesity. Interestingly, adipokines have also been found in periodontal ligament (PDL) cells and tissues [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resistin has a diverse role in the human body and influence cellular structure and function of various tissues. It has proinflammatory properties and stimulates the production and secretion of pro-inflammatory cytokines (8) resulting in abnormal endothelial function (9).It generates oxidative stress and induces the proliferation of vascular smooth muscle cells (VSMCs) thus reducing the levels of nitric oxide (NO) resulting in reduced vasodilation, increased cell adhesion, thrombosis, angiogenesis and vascular permeability ultimately leading to atherosclerosis and increase incidence of cardiovascular events (10).…”
Section: Introductionmentioning
confidence: 99%